2014
DOI: 10.1038/nchem.1961
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the intracellular distribution of tyrosine kinase inhibitors in living cells with quantitative hyperspectral stimulated Raman scattering

Abstract: ABL1 tyrosine-kinase inhibitors (TKI) are a front-line therapy for chronic myelogenous leukemia and represent the best known examples of targeted cancer therapeutics. However, the dynamic uptake of low molecular weight TKIs into cells and their intracellular behavior is largely unknown due to the difficulty of observing non-fluorescent small molecules at subcellular resolution. Here we report the direct label-free visualization and quantification of two TKI drugs – imatinib and nilotinib inside living cells us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
218
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(235 citation statements)
references
References 37 publications
9
218
0
4
Order By: Relevance
“…In line with our observations, it has been reported that drugs that sequester to lysosomes can reach final intracellular concentrations that are much higher than the drug concentrations in the surrounding medium (Kornhuber et al, 2010;Fu et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In line with our observations, it has been reported that drugs that sequester to lysosomes can reach final intracellular concentrations that are much higher than the drug concentrations in the surrounding medium (Kornhuber et al, 2010;Fu et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…It has been suggested that drug transfer directly from the cytosol into the luminal space of lysosomes may proceed via three different pathways: passive diffusion, autophagocytosis, and/ or transporter-mediated accumulation (Kaufmann and Krise, 2007). Since passive diffusion has the highest accumulation capacity and is most efficient, we and others (Fu et al, 2014) speculate that the uptake into lysosomes likely proceeds by simple diffusion, although other mechanisms cannot be excluded. Within the lysosome, imatinib will be effectively protonated and become membrane-impermeable (Szakacs et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being a nonlinear optical microscopy, it offers 3D sectioning capability with a diffraction-limited spatial resolution. SRS microscopy has been extensively applied to image biomolecules in cells and tissues (9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In this review, the potential for SRS as the latest development for in vitro drug screening is explored, pointing towards SRS as the future for spectroscopic HTS. In a particularly exciting study, Fu et al [97] used hyperspectral SRS to study the uptake and distribution of two tyrosine-kinase inhibitors (TKI), imatinib and nilotinib, in murine cell line BaF3 cells. Hyperspectral SRS images a number of Raman frequencies, providing additional biochemical information regarding the drug distribution inside cells by allowing both the drug and cellular signals to be recorded.…”
Section: An Alternative Technique -Surface Enhanced Raman Spectroscopmentioning
confidence: 99%